Overview of basic sanitation in the Mafututu village community, Tidore Island - Nani Supriyatni; Bartol Felndity; Verawati Liambana; Jenifer Pricilia Nona; Juhiarty S. Pita; Karmila Fataruba (BIOSAINSTEK, 2025)
Sanitation is an important factor in public health. Basic sanitation facilities involve three very important components, namely the provision of clean water, household waste disposal, and the provision of healthy latrines. The main issues in environmental health in Indonesian society generally still focus on decent housing, the provision of clean water, family latrines, waste disposal, and household waste management. The objective of this study is to provide an overview of the availability of basic sanitation as an effort in environmental health in Mafututu Village, Tidore District. This research is observational in nature. The study was conducted in Mafututu Village, Tidore District, in February 2025, with a sample of 178 respondents, using stratified random sampling techniques. The data collection methods included in-depth interviews and observations. The data processing was conducted descriptively. The research results indicate that the main water source used by households for drinking purposes is rainwater, accounting for 47.8%. The physical quality of drinking water is murky, with 42.1%. The most commonly used method for fecal waste disposal is septic tanks, at 91.0%. The waste disposal method used by households for organic waste is open trash bins, at 8.8%. The main method of handling household waste, which is often disposed of improperly, is 25.8%, while 25.3% is disposed of in the river. The method used by household members to prevent the transmission of diseases caused by mosquito bites includes using burning/spraying/electric mosquito repellent and the frequency of draining bathtubs.